Core–shell-structured nickel ferrite/onion-like carbon nanocapsules: an anode material with enhanced electrochemical performance for lithium-ion batteries. Issue 53 (11th June 2015) - Han, Dandan; Song, Gengxin; Liu, Bao; Yan, He
<x xml:space="preserve">Abstract</x> Core–shell-structured nanocapsules consisting of a nickel ferrite (NiFe2O4) nanoparticle core encapsulated in an onion-like carbon (C) shell are prepared by a modified arc-discharge method followed by an air-annealing process.